Digital Slang and English Informal Language in Online Gaming Communities An Analysis of Virtual Interaction - Restina Liza; Rona Adani Ulayya; Nil Andrian Afandi Matondang; Muhammad Hasyimsyah Batubara (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
This study examines the forms, functions, and sociolinguistic significance of digital slang and informal English as used within online gaming communities. Drawing on the theoretical frameworks of Crystal (2021), Herring (2007), and Gee (2003), the research identifies and analyzes key categories of gaming language—including abbreviations and acronyms (GG, AFK, OP), in-group jargon (noob, pwned, meta), onomatopoeia-based expressions, and code-switching practices—and investigates their communicative roles in virtual interaction. The findings demonstrate that digital slang in gaming communities serves not only as a communicative shortcut but also as a marker of identity, group solidarity, and social hierarchy. Informal language functions as a mechanism of inclusion and exclusion, delineating in-group members from outsiders, and reflecting the power dynamics inherent in digital social spaces. Furthermore, the study reveals that gaming slang transcends the virtual sphere, increasingly influencing everyday spoken and written English. By uncovering how informal language indexes community membership and cultural values in digital environments, this study contributes to the fields of internet linguistics, pragmatics, and the sociolinguistics of virtual communities.